Why the Global Meltdown not affected FDI segment in India - Rama Raju, Dr. K.S.S. (Journal of Contemporary Research in Management (JCRM), 2013)
For the developing economies, FDI inflows play a catalyst role in accelerating the pace of Industrial development. The expansion of international investments facilitated by the almost Universal Liberalization has resulted in a substantial increase in their global products, employment generation and trade. The Indian Government made several reforms in the economic policy of the country in the early 1990s. This helped in the liberalization and deregulation of the Indian economy and the country’ markets are opened to foreign direct investment India’s share in global FDI has marginally increased from 0.1 percent in 1990 to 0.8 percentin the year 2004 with average annual growth rate by US 2.3 billion a year. In the earlier years of the present decade, FDI inflows growth rate has mixed trend. Year 2004-05 recorded plus 48 percent growth rate, 70 percent in 2005-06, 65 percent in 2007-08 and even in recession period 2008-09, the growth rate is 11 percent. Negative growth rate not recorded in India which is significant when compared to many other countries with negative growth rate. With this background the objective of this study is to provide an analytical framework related to FDI inflows in India during 1991-2004, boom period from 2004-05 to 2007-08 with comparative analysis of the year 2008-09(recession prone). Paper also intends to focus to find out the countries that has maximum share in FDI inflows.